A novel strategy to reinforce glass fiber fabric/epoxy composites via modifying fibers with self‐assembled multi‐walled carbon nanotubes‐montmorillonite. Issue 2 (14th September 2019) - Zeng, Shaohua; Shen, Mingxia; Xue, Yijiao; Niu, Chenxu; Zheng, Yifei; Han, Yanxin; Tao, Wenzhu; Yang, Lu
Abstract: A novel strategy of multi‐walled carbon nanotubes‐montmorillonite (MWCNTs‐Mt)‐modified glass fiber fabrics (GFf) was used here to reinforce interlaminar regions of epoxy composites. One/two‐dimensional MWCNTs‐Mt hybrids with different mass ratios of MWCNTs and Mt were combined with the GFf, respectively, prior to a resin injection process. Making use of this strategy, uniformly dispersed MWCNTs and highly exfoliated Mt at the fiber/matrix interface could be achieved; meanwhile, mechanical and interfacial properties of resultant composites were greatly enhanced. Under a mass ratio of MWCNTs:Mt (0.2:1), the interlaminar shear, tensile, and flexural strengths of resultant composites were improved by 31.0%, 26.0%, and 21.9%, respectively; the storage modulus increased by 23.6%, compared with the composite without MWCNTs‐Mt. Also, the work of fracture obtained from interlaminar load‐displacement curves and peak loss moduli of resultant composites were significantly enhanced, indicating the synergistic toughening effect of MWCNTs and Mt.